Uji Model Keberhasilan Sistem Informasi: Media Penyimpanan Google Drive - Trilaksono, Agustinus Rio; Husain, T.; Doharma, Rouly (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
The era of ICT-based information (information and communication technology), information becomes an absolute primary means for users decent individuals and organizations as a medium of exchange and interaction. Google Drive is one of the internet-based services application that allows users to make storage media as a resources. The destination of this research to calibration the IS Success Model of Google Drive as a storage medium among college students with the elements i.e. Information Quality, System Quality and Service Quality. The research method used a quantitative approach with questionnaires as a means of data collection. The number of samples counted by 77 respondents. The data analysis methods using structural equation modeling by Lisrel Version 8.72 through descriptive statistic analysis, test of quality instrument, goodness-of fit model, and hypotesis test. The findings represent that the IS Success Model prove significant influence on Satisfaction of college student through Information Quality and System Quality while Quality Service is not significant influence. Service Quality and System Quality are the most effective variables affecting Satisfaction of college student with correlation coefficient in the amount of 67,8 percent and 66,5 percent.